Design of an Integrated Microvascularized Human Skin-on-a-Chip Tissue Equivalent Model - Jones, Christian F. E.; Di Cio, Stefania; Connelly, John T.; Gautrot, Julien E. (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue engineered skin constructs have been under development since the 1980s as a replacement for human skin tissues and animal models for therapeutics and cosmetic testing. These have evolved from simple single cell-assays to increasingly complex models with integrated dermal equivalents and multiple cell types including a dermis, epidermis and vasculature. The development of micro-engineered platforms and biomaterials has enabled scientists to better recreate and capture the tissue microenvironment in vitro, including the vascularization of tissue models and their integration into microfluidic chips. However, to date, microvascularised human skin equivalents in a microfluidic context have not been reported. Here we present the design of a novel skin-on-a-chip model integrating human derived primary and immortalized cells in a full thickness skin equivalent. The model is housed in a microfluidic device, in which a microvasculature was previously established. We characterize the impact of our chip design on the quality of the microvascular networks formed and evidence that this enables the formation of more homogenous networks. We developed a methodology to harvest tissues from embedded chips, after 14 days of culture, and characterize the impact of culture conditions and vascularization (including with pericyte co-cultures) on the stratification of the epidermis in the resulting skin equivalents. Our results indicate that vascularization enhances stratification and differentiation (thickness, architecture and expression of terminal differentiation markers such as involucrin and transglutaminase 1), allowing formation of more mature skin equivalents in microfluidic chips. The skin-on-a-chip tissue equivalents developed, thanks to their realistic microvasculature, may find application for the testing efficacy and safety of therapeutics delivered systemically, in a human context.